2002
DOI: 10.1089/10807680260362722
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Topically Administered Ofloxacin and Trimethoprim Into Aqueous Humor

Abstract: Ocular penetration of two topical antibiotics used to treat bacterial conjunctivitis was assessed in adult volunteers scheduled for cataract surgery. In this randomized, parallel-group study, patients instilled trimethoprim sulfate 0.1%/polymyxin B (n = 23) or ofloxacin 0.3% (n = 25) QID for 3 days, plus 4 instillations in the hour before surgery. Analysis of aqueous humor samples obtained during surgery showed a 2.4-fold greater concentration of ofloxacin over trimethoprim (1.135 micro g/ml vs 0.470 micro g/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…For example, fluoroquinolones achieve better penetration into ocular tissue than older antibiotics (e.g., tobramycin and trimethoprim), and the newer fluoroquinolones tend to penetrate ocular tissues better than the older fluoroquinolones. 46,[92][93][94][95][96] Concentrations of moxifloxacin in the conjunctiva (6.6 Ϯ 0.3 g/g) were found to be two times higher than those achieved with tobramycin; three to four times higher than with ofloxacin, levofloxacin, and gatifloxacin; and more than 16 times higher than with trimethoprim. 46 Combined PK and PD data can be used to characterize tissue levels of antibiotics relative to microbial susceptibility characteristics.…”
Section: Using Pharmacokinetic/pharmacodynamic Properties To Predict mentioning
confidence: 85%
“…For example, fluoroquinolones achieve better penetration into ocular tissue than older antibiotics (e.g., tobramycin and trimethoprim), and the newer fluoroquinolones tend to penetrate ocular tissues better than the older fluoroquinolones. 46,[92][93][94][95][96] Concentrations of moxifloxacin in the conjunctiva (6.6 Ϯ 0.3 g/g) were found to be two times higher than those achieved with tobramycin; three to four times higher than with ofloxacin, levofloxacin, and gatifloxacin; and more than 16 times higher than with trimethoprim. 46 Combined PK and PD data can be used to characterize tissue levels of antibiotics relative to microbial susceptibility characteristics.…”
Section: Using Pharmacokinetic/pharmacodynamic Properties To Predict mentioning
confidence: 85%
“…Collectively, their results show that moxifloxacin rapidly penetrates the cornea and aqueous humor to achieve concentrations that far exceed the MIC and mutant prevention concentration (defined as the MIC of the least-susceptible mutant subpopulation of a microbial culture 54 ) values for the most important endophthalmitis pathogens. In addition, the ocular concentrations of moxifloxacin achieved were consistently at least 2-fold higher than those occurring with topically instilled gatifloxacin, 9-fold higher than those achieved with ciprofloxacin, and based on historical controls, up to 27-fold higher than those achieved in clinical studies of aqueous humor penetration of topical ofloxacin 0.3% or levofloxacin 0.5% ophthalmic solutions [55][56][57] A study by Kim et al 53 found that after the preoperative administration of just 4 doses 1 hour before surgery, moxifloxacin 0.5% achieved a mean aqueous humor concentration 4-fold higher than that of gatifloxacin 0.3% (mean 1.80 G 1.21 mcg/mL versus 0.48 G 0.34 mcg/mL) (P Z .00003). The mean levels achieved with both fluoroquinolones exceeded the respective minimum bactericidal concentration for 90% of tested strains (MBC 90 ) value for fluoroquinolonesusceptible S aureus, but only moxifloxacin achieved a concentration exceeding the MBC 90 for S epidermidis, S pneumoniae, Propionibacterium acnes, and Serratia Relevant to the ESCRS study, no published studies directly compare aqueous humor penetration of topical moxifloxacin and topical levofloxacin.…”
Section: Penetrationmentioning
confidence: 95%
“…Studies in animal models using exaggerated dosing regimens demonstrate an absence of corneal toxicity and suggest moxifloxacin may have a better corneal safety profile than other topical fluoroquinolones, a benefit that may be related to its benzalkonium chloride-free formulation. 51,[55][56][57][58] Confocal analyses were conducted to examine the effects of moxifloxacin on the normal human cornea. Studies of patients having cataract and refractive surgery also demonstrate that moxifloxacin has no adverse effects on corneal or conjunctival healing.…”
Section: Safetymentioning
confidence: 99%
“…Resistance rates among ocular isolates to either polymyxin B or trimethoprim in isolation are relatively low in comparison to those for the fluoroquinolones, with 3% of P. aeruginosa isolates demonstrating polymyxin B resistance and trimethoprim resistance rates of 3% and 7% for methicillin-susceptible S. aureus (MSSA) and MRSA, respectively (12). Despite the limited bacterial resistance, PT is rarely considered a bacterial keratitis treatment option because of its low antimicrobial potency, slow killing kinetics, weak antibiofilm activity, and limited tissue penetration relative to those of fluoroquinolones (20)(21)(22)(23).…”
mentioning
confidence: 99%